Evaluation of Cardiac Auscultation Skills in Pediatric Residents. (January 2013) - Kumar, Komal; Thompson, W. Reid
Auscultation skills are in decline, but few studies have shown which specific aspects are most difficult for trainees. We evaluated individual aspects of cardiac auscultation among pediatric residents using recorded heart sounds to determine which elements pose the most difficulty. Methods . Auscultation proficiency was assessed among 34 trainees following a pediatric cardiology rotation using an open-set format evaluation module, similar to the actual clinical auscultation description process. Results . Diagnostic accuracy for distinguishing normal from abnormal cases was 73%. Findings most commonly correctly identified included pathological systolic and diastolic murmurs and widely split second heart sounds. Those least likely to be identified included continuous murmurs and clicks. Accuracy was low for identifying specific diagnoses. Conclusions . Given time constraints for clinical skills teaching, this suggests that focusing on distinguishing normal from abnormal heart sounds and murmurs instead of making specific diagnoses may be a more realistic goal for pediatric resident auscultation training.